PTH Serum Levels and Mortality Risk among Incident Hemodialysis Patients - Roldão,Marisa (2022)
ABSTRACT Introduction: Chronic kidney disease (CKD)-mineral and bone disorder (MBD) is a major complication in hemodialysis (HD) patients. Serum intact parathyroid hormone (iPTH) has been associated with prognosis in these patients, however, the optimal range to reduce mortality remains unknown. Methods: We conducted a retrospective study of incident HD patients, who were categorized into 4 groups according to iPTH serum level: <150 pg/mL, 150-300 pg/mL, 301-600 pg/mL and >600 pg/mL. All-cause and cardiovascular mortality over a mean follow-up of 3 years was assessed using standard survival methods. Results: One hundred and forty-nine patients were included. Patients with low iPTH presented low serum albumin, phosphorus, and bonespecific alkaline phosphatase (BAP), increased c-reactive protein (CRP) and higher serum bicarbonate (p<0.05). Those with iPTH <150 pg/mL had an increased risk of all-cause and cardiovascular mortality, when compared to those with iPTH 301-600 pg/mL (HR: 0.59; 95% CI: 0.36-0.96; p=0.035) and iPTH >600 pg/mL (HR: 0.39; 95% CI: 0.20-0.78; p=0.008), even after adjusting for potential confounding factors as age, albumin, and comorbidities (diabetes, congestive heart failure (CHF), and hypertension). Discussion: PTH levels were associated with all-cause and cardiovascular mortality risk in our cohort of incident HD patients. Our results suggest that patients with low iPTH at HD initiation had an increased mortality risk, which may reflect a frail group of patients with anorexia, sarcopenia, malnutrition, and inflammation.